Bone Morphogenetic Protein 6 Inhibits the Immunomodulatory Property of BMMSCs via Id1 in Sjögren's Syndrome - Yingying Su; Yi Gu; Ruiqing Wu; Hao Wang (Hindawi Limited, 2018)
Mesenchymal stem cells (MSCs) treatment has emerged as a promising approach for treating Sjögren's syndrome (SS). Impaired immunoregulatory activities of bone marrow mesenchymal stem cells (BMMSCs) are found in both SS patients and animal models, and the underlying mechanism is poorly understood. Increased expression of BMP6 is reported to be related to SS. The aim herein was to determine the effects of BMP6 on BMMSCs function. BMMSCs were isolated from SS patients and NOD mice and showed a high level of BMP6 expression. The effects of BMP6 on BMMSCs function were investigated using in vitro BMMSCs differentiation and in vitro and in vivo T cell proliferation and polarization assays. BMP6 increased osteogenic differentiation of BMMSCs and inhibited the immunomodulatory properties of BMMSCs. BMP6 enhanced T cell proliferation and Th1/Th17 differentiation in a T cell-BMMSC coculture system. Mechanistically, BMP6 downregulated PGE2 and upregulated IFN-gamma via Id1 (inhibitor of DNA-binding protein 1). Neutralizing BMP6 and knockdown of Id1 could restore the BMMSCs immunosuppressive function both in vitro and in vivo. The present results suggest a novel role of Id1 in BMP-mediated MSCs function, which may contribute to a better understanding of the mechanism of action of MSCs in treating autoimmune diseases.